Adoption Of Small Family Norms In A Rural Community Of West Bengal - Biswas A.K; Roy A; Biswas R (Wolters Kluwer Medknow Publications, 1994)
Research Questions: 1. To what extent do rural eligible couples accept the small family norm? 2. What are the factors which influence the adoption of small family norm by these couples? Objectives: 1. To determine the extent of adoption of small norm among family planning service acceptors (2) To identify factors influencing adoption of small family norm. Study Design: Cross sectional Study Setting: 2 villages- a PHC village and one 5 kms away of Block Sonarpur. Participants: 312 eligible couples of these villages. Study Variables: Socio â€" economics status, literacy of the wives, type of family, religion, number of children, type of family planning method. Outcome Variables: Prevalence of contraceptive method use, reasons for not using family planning methods. Statistical Analysis: Proportions Results : The prevalence of contraceptive use was 44.9% but the Effective Couple Protection Rate was only 20.5% and the Crude Birth Rate was still high (35/1000). This was because 40% of the couples had more then 2 children and of them 38% were still exposed to the risk of conception. Muslim couples had a lower contraceptive acceptance rate than Hindu couples. The more literate the wife, the greater the acceptance of the small family norm. Male preference pressure from elders and fear about contraception were the main reasons for non acceptance of family planning methods: The health teams were the main source of information to these couples. Recommendations: There is an urgent need to increase the emphasis on the 2 child family norm. The IEC activities of the health team should be strengthened.